2013
DOI: 10.1002/ejic.201300180
|View full text |Cite
|
Sign up to set email alerts
|

A Synthetic Cycle for Nitrogen Atom Transfer Featuring a Diruthenium Nitride Intermediate

Abstract: A new Ru2 azido complex, [Ru2(chp)4N3] (4, chp = 2‐chloro‐6‐hydroxypyridinate), was investigated under photolytic conditions to study the chemical reactivity of the corresponding Ru2 nitride species, [Ru2(chp)4N] (6), towards intermolecular N atom transfer to triphenylphosphane (PPh3). Photolysis of a dichloromethane solution of 4 at λ > 350 nm leads to a characteristic color change from purple to magenta. Upon acidic workup, triphenylphosphanamine chloride ([H2NPPh3]Cl) is produced and [Ru2(chp)4Cl] (5), t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(48 citation statements)
references
References 32 publications
3
45
0
Order By: Relevance
“…This is also similar to the case of Ru 2 -azide compounds that show Ru 2 N signals in their mass spectra due to photolysis. 2 To further support this hypothesis, we used labeled 18 O-nitrate (N 18 O 3 − ) to form Ru 2 (chp) 4 18 ON 18 O 2 ( 4 *), and we found that the Ru 2 O feature shifts in the mass spectrum to m/z = 735 amu (Figure 5). This shift clearly indicates that the axial O atom in the [Ru 2 (chp) 4 O] + ion derives from nitrate and is fully consistent with photo-dissociation of NO 2 • or NO 2 − from 4 .…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…This is also similar to the case of Ru 2 -azide compounds that show Ru 2 N signals in their mass spectra due to photolysis. 2 To further support this hypothesis, we used labeled 18 O-nitrate (N 18 O 3 − ) to form Ru 2 (chp) 4 18 ON 18 O 2 ( 4 *), and we found that the Ru 2 O feature shifts in the mass spectrum to m/z = 735 amu (Figure 5). This shift clearly indicates that the axial O atom in the [Ru 2 (chp) 4 O] + ion derives from nitrate and is fully consistent with photo-dissociation of NO 2 • or NO 2 − from 4 .…”
Section: Resultsmentioning
confidence: 93%
“…As with the chloride precursor 3 22 and azide analog Ru 2 (chp) 4 N 3 , 2d the equatorial chp ligands in 4 and 5 are bound in a (4,0) orientation, which allows for the oxyanionic ligand to bind only to the exposed Ru axial site.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the characterization of the main product, the observation of a broad singlet in the 1 H NMR spectrum at δ = 8.25 ppm in [D 8 ]THF proved to be instructive, which shows 1 J coupling to the amido nitrogen atom (δ 15N = 122 ppm; 15 N, 1 H HSQC). A similar observation was made by us for the reaction of complex 1 and a related Ir nitrido complex with silanes (R 3 SiH, R = Et, Ph), which resulted in silyl amido complexes.…”
Section: Synthesis and Characterizationmentioning
confidence: 98%
“…Recent reports evidenced the potential of isolated and putative nitrido complexes in intramolecular C-H [11] and dihydrogen [7,8] activation. Further prominent reactions include an hydrogen atom abstraction, [12] the dimerization to dinitrogen complexes, [13] nitrogen transfer, [14,15] and the reactions with the nucleophiles Me 3 NO [8,10] and Ph 3 P. [4,15] For the later reaction Smith et al have recently shown, that both, electron donation to and from the nitrido nitrogen atom take place in the transition state. [16] Recently, we have shown that square-planar iridium complexes with a terminal nitrido unit also react with silanes under insertion of the nitrido nitrogen atom into the Si-H bond.…”
Section: Introductionmentioning
confidence: 98%